The Influence of Unemployment and Poverty on Economic Growth in East Java Province - Kenshawitri Febrian P. P.; Meliana Anggita Prasasti; Nabilla Audiana Putri (Prosiding Seminar Nasional Ilmu Manajemen, Ekonomi, Keuangan dan Bisnis, 2023)
This study aims to analyze the effect of unemployment and poverty on economic growth in East Java Province. The data used in this study include unemployment, poverty, and economic growth indicators. The data obtained were then analyzed with multiple linear equation analysis using the SPSS software program using annual data for a certain period. The results of the analysis show that the effect of unemployment and poverty on economic growth in East Java Province is not significant, so it can be concluded that there are other factors that are more dominant in influencing economic growth in East Java Province. This study also found that poverty and unemployment rates had no effect on economic growth in East Java Province.